2018
DOI: 10.1177/0300060518786904
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of pentoxifylline in small intestine after ischemia–reperfusion

Abstract: ObjectiveThis study was performed to determine the healing effects of pentoxifylline on molecular responses and protection against severe ischemic damage in the small intestine.MethodsThirty-six Wistar albino rats were divided into six groups. The superior mesenteric artery was clamped for 120 minutes, and reperfusion was performed for 60 minutes. Saline (0.4 mL), pentoxifylline (1 mg/kg), and pentoxifylline (10 mg/kg) were intraperitoneally administered to the rats in the C1, P1, and P3 groups, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The administration of intradermal hyaluronidase combined with intraperitoneal pentoxifylline for 14 days showed a decrease in the cellularity of macrophages on the dermis, while the administration of pentoxifylline alone stimulated angiogenesis 17 . The biochemical and histopathological findings suggest that low doses of pentoxifylline can effectively improve ischemic damage in the experimental model of skin flaps 30 . The administration of 20 mg/kg/day of pentoxifylline by intraperitoneal route in rats undergoing myocutaneous flap of the caudal monopedicled rectus abdominis showed changes in the microcirculation system, decreased necrosis, and increased number of capillaries in the flap ischemia zone (zone IV) 31 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The administration of intradermal hyaluronidase combined with intraperitoneal pentoxifylline for 14 days showed a decrease in the cellularity of macrophages on the dermis, while the administration of pentoxifylline alone stimulated angiogenesis 17 . The biochemical and histopathological findings suggest that low doses of pentoxifylline can effectively improve ischemic damage in the experimental model of skin flaps 30 . The administration of 20 mg/kg/day of pentoxifylline by intraperitoneal route in rats undergoing myocutaneous flap of the caudal monopedicled rectus abdominis showed changes in the microcirculation system, decreased necrosis, and increased number of capillaries in the flap ischemia zone (zone IV) 31 .…”
Section: Discussionmentioning
confidence: 88%
“…Other 8,9,11,13,14,[16][17][18][19][28][29][30][31][32] have demonstrated that parenteral administration of pentoxifylline with different schemes and doses ranging from 1 to 50 mg/kg, was able to improve tissue vitality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation